Deep peroneal neuropathy induced by prolonged squatting: a case report - Jo, Hyun-Seok; Kim, Ki-Hong; Song, Min-Keun; Park, Hyeng-Kyu; Choi, In Sung; Han, Jae-Young (Frontiers in Neuroanatomy, 2024)
Prolonged squatting is a well-documented cause of common peroneal neuropathy, wherein the common peroneal nerve is thought to be compressed between the biceps femoris tendon and the lateral head of the gastrocnemius muscle or the fibular head. However, deep peroneal neuropathy resulting from prolonged squatting has not been previously reported. We present the case of a tile installer who developed unilateral deep peroneal neuropathy following extended squatting, diagnosed through ultrasonography, which identified the bilateral division of the common peroneal nerves between the knee joint and the fibular head. This case underscores the value of ultrasonography, particularly when electrodiagnostic results are inconsistent with clinical expectations.